Health system- and patient-related factors associated with COVID-19 mortality among hospitalized patients in Limpopo Province of South Africa’s public hospitals - Sono-Setati, Musa E.; Mphekgwana, Peter M.; Mabila, Linneth N.; Mbombi, Masenyani O.; Muthelo, Livhuwani; Matlala, Sogo F.; Tshitangano, Takalani G.; Ramalivhana, Naledzani J. (MDPI, 2022)
South Africa has recorded the highest COVID-19 morbidity and mortality compared to other African regions. Several authors have linked the least amount of death in African countries with under-reporting due to poor health systems and patients’ health-seeking behaviors, making the use of clinical audits more relevant for establishing the root causes of health problems, and improving quality patient care outcomes. Clinical audits, such as mortality audits, have a significant role in improving quality health care services, but very little is documented about the outcomes of the audits. Therefore, the study sought to determine the health care system and patient-related factors associated with COVID-19 mortality by reviewing the COVID-19 inpatient mortality audit narration reports. This was a retrospective qualitative research approach of all hospitalized COVID-19 patients, resulting in death between the first and second COVID-19 pandemic waves. Thematic analysis employed inductive coding to identify themes from mortality audits from all 41 public hospitals in Limpopo Province, South Africa. Four themes with seventeen sub-themes emerged: sub-standard emergency medical care provided, referral system inefficiencies contributed to delays in access to health care services, the advanced age of patients with known and unknown comorbidities, and poor management of medical supplies and equipment, as a health system and patient-related factors that contributed to the high mortality of COVID-19 patients. There is a need to routinely conduct clinical audits to identify clinical challenges and make recommendations for health promotion, risk communication, and community engagement. We recommend reviewing and expanding the scope of practice for health-care providers during epidemics and pandemics that include aspects such as task-shifting.
Journal article published in the journal of Healthcare, 2022, 10, 1388
Keywords: COVID-19; Mortality; Hospitalized; Health system; Patient-related factors; COVID-19 (Disease); COVID-19 -- Mortality; Hospital patients; Health care reform